PROTOTYPE OF CONDENSATION DETECTOR ON AIR HANDLING UNIT DUCTING BASED ON BLYNK AT JUWATA TARAKAN AIR PORT TERMINAL - Fauzan, Rafi; Kurniaty Atmia; Sheila Novita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research designs a prototype condensation detection system on Air Handling Unit (AHU) ducting at Juwata Tarakan Airport by utilizing Internet of Things (IoT) technology based on the Blynk platform. Condensation problems in AHU systems often cause water droplets that impact passenger comfort and safety, but there is no effective monitoring system for early detection. This system uses DHT11 and Raindrop sensors integrated with an ESP32 microcontroller, which will send temperature, humidity, and water presence data to the Blynk application in real-time. Test results show that the system is able to detect potential condensation quickly and accurately, and send notifications to technicians in less than two seconds. In addition to improving AHU maintenance efficiency, this system also supports increased security and comfort in the terminal area. This research is expected to be a practical solution for intelligent HVAC system monitoring in public facilities.